Electrophoretic Deposition of Nitrogen-Boron Co-Doped Graphene as High Performance Electrode for Next Generation Supercapacitors. (19th June 2018) - Kumar, Amit; Kumar, Nagesh; Singh, Pragya; Leu, Jihperng; Tseng, Tseung-Yuen
Abstract : In this study, we report the electrophoretic deposition (EPD) of nitrogen-boron co-doped graphene (NBG) synthesized via simple hydrothermal method and subsequent annealing at 750℃ in reducing environment. The structural, chemical-compositional and morphological investigations of the as synthesized NBG are investigated using X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). The electrochemical properties of the samples are studied via cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) cycling and electrochemical impedance spectroscopy (EIS) in a conventional three-electrode system using 6M KOH aqueous electrolyte. The EPD grown binder free NBG electrode exhibits high specific capacitance of 217 Fg -1 at the scan rate of 5 mVs -1 which is about 1.2 times higher than the specific capacitance (180 Fg -1 at 5 mVs -1 ) of pristine reduced graphene oxide. Furthermore, this sample exhibits excellent rate capability and 103% retention after 8800 successive charge-discharge cycles at 1 Ag -1 .